General purpose psychiatric questionnaire G. P. P. Q - Soejono Prawirohardjo, Soejono Prawirohardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1973)
keywords: masalah kemiskinan, psychosis, syaraf